S22 Improved symptoms and quality of life after pulmonary endarterectomy (PEA) in patients with chronic thromboembolic disease (CTED) and borderline pulmonary hypertension (PH). (2nd December 2011) - Taboada, D; Treacey, C; Jenkins, D; Zaba, J Pepke; Sheares, K
Abstract : Background: Chronic thromboembolic pulmonary hypertension (CTEPH) is defined by a mean pulmonary artery pressure (mPAP) =25 mm Hg at right heart catheterisation in patients with multiple chronic/organised occlusive thrombi in the pulmonary arteries. PEA is potentially curable and is the treatment of choice for patients with CTEPH. There is a small group of patients with CTED and exertional dyspnoea but with a resting mPAP that does not fulfil criteria for PH in whom PEA may be considered. The outcome of PEA in these patients has not been previously assessed. Objective: To assess the post PEA functional and haemodynamic outcomes in patients with symptomatic CTED and borderline PH. Methods: Retrospective data were collected on patients with baseline mPAP of =25 mm Hg who underwent PEA at the UK and Ireland national referral centre between 2002 and 2010. Patients were reassessed 3 and 12 months after surgery. Right heart catheterisation was performed at baseline and 3 months post PEA. Results: 558 patients underwent PEA at Papworth Hospital between 2002 and 2010. From those, 16 had symptomatic operable CTED and mPAP of =25 mm Hg. Mean age was 45±17 and 69% were female. All survived surgery and are currently alive at follow-up. The median length of stay was 13 days (IQR 6). Results are displayed in the Abstract S22 table 1 as mean ± SD. WHO class data are expressed as percentages. CAMPHOR (Cambridge Pulmonary Hypertension Outcome Review) is a disease specific quality of life questionnaire and scores are expressed as median. Conclusion: In this small series of patients with CTED and borderline PH, there was a significant symptomatic, haemodynamic and functional benefit from PEA at 1-year. Further research is required to assess the prognostic benefit in this population. We would like to acknowledge the national pulmonary hypertension centres in the UK and Ireland, and support by the Cambridge NIHR Comprehensive Biomedical Research Centre.